2006
DOI: 10.1002/jrs.1452
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the amide I Raman tensor for the antiparallel β‐sheet: application to silkworm and spider silks

Abstract: The amide I Raman tensor corresponding to the antiparallel b-sheet structure in proteins has been determined by polarized Raman microspectroscopy of fowl feather rachis using polarized Raman spectra excited in the near-infrared (785 nm). For a Raman tensor principal axis system (XYZ), in which X is perpendicular to the plane of the pleated b-sheet, Y is in the plane of the sheet and perpendicular to the direction of the polypeptide chain, and Z is parallel to the direction of the polypeptide chain, the princip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
48
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(51 citation statements)
references
References 29 publications
2
48
0
1
Order By: Relevance
“…Approximate D 2 symmetry of the antiparallel -sheet gives rise to four vibrational modes in the amide I region, A (1675 cm -1 ), B (∼1690 cm -1 , not observed), B 2 (1633 cm -1 ), and B 3 (unknown). 17 Two of them, A (1675 cm -1 ) and B 2 (1635 cm -1 ), are well resolved in the cross-core spectrum indicating that the antiparallel -sheet structure dominates the lysozyme fibril core. The other two amide I bands may be obscured by the strong 1675 cm -1 band resonantly enhanced via Albercht A term.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…Approximate D 2 symmetry of the antiparallel -sheet gives rise to four vibrational modes in the amide I region, A (1675 cm -1 ), B (∼1690 cm -1 , not observed), B 2 (1633 cm -1 ), and B 3 (unknown). 17 Two of them, A (1675 cm -1 ) and B 2 (1635 cm -1 ), are well resolved in the cross-core spectrum indicating that the antiparallel -sheet structure dominates the lysozyme fibril core. The other two amide I bands may be obscured by the strong 1675 cm -1 band resonantly enhanced via Albercht A term.…”
mentioning
confidence: 95%
“…The other two amide I bands may be obscured by the strong 1675 cm -1 band resonantly enhanced via Albercht A term. 17 The C R -H band is composed of at least three narrow sub-bands centered at Figure 1. DUVRR spectra of (a) thermally denatured hen egg white lysozyme in H2O (blue) and D2O (red), and (b) lysozyme fibrils in H2O (blue), 50% D2O/H2O mixture (green), and 100% D2O (red).…”
mentioning
confidence: 99%
“…The tensor components r 1 = α xx / α zz and r 2 = α yy / α zz are denoted by blue and red numerals, respectively. References to the original literature, where details of the tensor calculations are described, are as follows: (A) Ueda et al ; 9) (B) Benevides et al ; 16) (C) Tsuboi et al ; 3),47) (D1) Benevides et al ; 44) (D2) Thomas et al ; 10) (E1) Ushizawa et al ; 14) (E2) Benevides et al ; 44) (F1) Tsuboi et al ; 3) (F2) Tsuboi et al ; 3) (G1) Overman et al ; 25) (G2) Tsuboi et al ; 57) (G3) Yokote et al ; 41) (G4) Yokote et al ; 41) (H1)(H2)(H3) Tsuboi et al ; 8) (I1)(I2)(I3) Tsuboi et al ; 15) (J1) Thomas et al ; 10) (J2) Benevides et al ; 16) (K1)(K2) Benevides et al ; 44) (L1) Thomas et al ; 10) (L2)(L3) Tsuboi et al ; 12) (L4) Kumakura et al ; 49) (M1) Thomas et al ; 10) (M2) Benevides et al ; 44) (M3) Ushizawa et al ; 46) (N1) Ueda et al ; 51) (N2) Benevides et al ; 44) (N3) Ushizawa et al ; 55) (O1) Thomas et al ; 10) (O2)(O3)(O4) Benevides et al ; 16) (O5)(O6) Benevides et al 44) …”
Section: A Catalog Of Raman Tensorsunclassified
“…This technique was used by Tsuboi et al 30 to determine the amide I Raman tensor for the antiparallelˇ-sheet structure in proteins of fowl feather rachis. The Raman tensor determined in this way is also applied to Raman studies of other naturalˇ-sheet structures, and it is successfully shown that in this way the relative contribution ofˇ-turns can be determined.…”
Section: Biochemistry/biologymentioning
confidence: 99%